Sonographic Assessment of Renal Length of Adults in Lagos, Nigeria (Nepalese Medical Journal, 2019)
Introduction: Ultrasound is an important imaging modality used in the prognosis and diagnosis of renal conditions and diseases and also in the evaluation of kidney donors. This study aimed at providing a reference for the normal metric variables of the kidney such kidney lengths of healthy Nigerian adults in Lagos State and to compare with previously obtained results.Materials and Methods: This study was conducted in the radiology department of Ikorodu Hospital. This study adopted a descriptive cross-sectional study design with a cluster sampling approach which consisted of 150 adults (with 300 kidneys) participants ages 18-87 years. Real-time gray-scale ultrasonic scanning using Prosound 3500 Aloka device and a 3.5–5 MHz curvilinear explorer was employed for the abdominal imaging. The data acquired were compiled and explored via the Statistical Package for the Social Sciences (SPSS) version 20. The student’s t-test was utilized in probing for statistical significance between age as well as gender in relation to renal length. P-value < 0.05 was adjudged to be significant.Results: The kidney length was of a greater distance in males, and the length of the left kidney was more extensive than that of the right kidney in both sexes. Average kidney length was greater on the left when compared to the right among the various age groups. No significant association was noted between kidney length and age as well as gender.Conclusions: Normal values for kidney length and diversifications in the kidney length of healthy adults in Nigeria have been established.